ENHANCE SERVICE QUALITY WITH CONFLICT MANAGEMENT IN THE COMPANY - Fitra Arlina Nasution (Sean Institute, 2023)
In this paper, conflict research is part of human nature in social life which can improve good management and be used as a stimulus to improve the quality of performance. This research examines the sources of conflict and the urgency of conflict management in Islamic educational institutions. This research is a library research with a descriptive approach. Conflict management in corporate institutions is one of the effective ways to increase work productivity. The key to the effectiveness of conflict management in Islamic educational institutions is the ability and innovation of institutional leaders in combining or choosing the best among several conflict management strategies such as giving explanations (tabayyun), deliberation, tahkim, ishlah, and other strategies.